Cord Blood Cytokine Levels Correlate With Types of Placental Pathology in Extremely Preterm Infants - Zein, Hussein; Mohammad, Khorshid; Leijser, Lara M.; Brundler, Marie-Anne; Kirton, Adam; Esser, Michael J. (Frontiers in Pediatrics, 2021)
Background: Placental abnormalities are associated with inflammation and have been linked to brain injury in preterm infants. We studied the relationship between placental pathology and the temporal profiles of cytokine levels in extremely pre-term infants. Study Design: We prospectively enrolled 55 extremely preterm infants born between June 2017 and July 2018. Levels of 27 cytokines were measured in blood drawn from the umbilical artery at birth and from infants at 1–3 and 21–28 days of life. Placental pathology was grouped as normal (N), inflammation (I), vasculopathy (V), or combined vasculopathy and inflammation (V+I). Results: Complete data was available from 42 patients. Cord blood median levels of cytokines differed between groups with the highest levels observed in group V+I as compared to groups N, I and V for the following: Eotaxin (p = 0.038), G-CSF (p = 0.023), IFN-γ (p = 0.002), IL-1ra (p < 0.001), IL-4 (p = 0.005), IL-8 (p = 0.010), MCP-1 (p = 0.011), and TNFα (p = 0.002). Post-hoc analysis revealed sex differences between and within the placental pathology groups. Conclusion: Specific types of placental pathology may be associated with differential cytokine profiles in extremely pre-term infants. Sampling from cord blood may help assess the pathological status of the placenta and potentially infer outcome risks for the infant.